Geomorphology of Pereiro Massif, Northeast Brazil - Brito, Edmundo Rodrigues de; Bastos, Frederico de Holanda; Claudino Sales, Vanda Carneiro de; Cordeiro, Abner Monteiro Nunes; Siame, Lionel (Revista Brasileira de Geomorfologia, 2025)
The Pereiro Massif (Northeast Brazil) is a granite relief situated between the Jaguaribe and Portalegre shear zones, exhibiting strong structural control over its morphology. This study aims to analyze the morphostructural context of the massif and interpret its evolution based on denudation rates, using in situ cosmogenic isotope (10Be) production, OSL dating of colluvial deposits, and GIS-based morphometric analyses. The results suggest that the massif represents a relief inherited from a lithostructural framework associated with the Brazilian orogeny, with Cretaceous reactivations and Cenozoic denudational cycles. Its formation is primarily attributed to differential erosion, driven by the greater resistance of granitoids compared to the surrounding metamorphic lithologies. There is no clear evidence of neotectonic activity influencing regional morphogenesis. Denudation rates range from 10.1 to 24.6 m∙My-1, indicating higher denudation trends influenced by lithostructural and topographic controls. Post-Miocene morphodynamics were shaped by the regional semi-arid climate, punctuated by humid paleoclimatic variations that account for colluviation between the Last Glacial Maximum (LGM) and the Younger Dryas.